MIXED MODIFICATION PLANTING MEDIA TO THE GROWTH OF CELERY PLANTS (Apium gravolens L.) ON VERTICULTURE SYSTEM - Nurlaili, Nurlaili; Gribaldi, Gribaldi (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2015)
Celery plants are not only can be grown in large fields but can also be grown in small fields such as plant cultivation through verticulture. Cultivation technique with verticulture system is a vertical farming technique using up land and suitable for less fertile land. The efforts to improve the planting growth on this verticulture system can be done by improving the planting media. This study aims to determine the effect of various planting media to improve the growth of celery plants through verticulture system. The study was conducted using Completely Randomized Design (CRD) which are arranged in non-factorial with 4 treatments and 4 replications. The treatment under study consists of: A = Sand, B = Soil + Sand, C = Soil + Manure, and D = Land. The result showed that the treatment of some planting media influence on the growth of celery plants on verticulture system. Planting media such as soil + manure is the best planting media and able to improve the growth of celery planting on verticulture system.